Recessive Mutations in ACP4 Cause Amelogenesis Imperfecta. (January 2022) - Kim, Y.J.; Lee, Y.; Kasimoglu, Y.; Seymen, F.; Simmer, J.P.; Hu, J.C.-C.; Cho, E.-S.; Kim, J.-W.
Amelogenesis imperfecta (AI) is an innate disorder that affects the formation and mineralization of the tooth enamel. When diagnosed with AI, one's teeth can be hypoplastic (thin enamel), hypomature (normal enamel thickness but discolored and softer than normal enamel), hypocalcified (normal enamel thickness but extremely weak), or mixed conditions of the above. Numerous studies have revealed the genes that are involved in causing AI. Recently, ACP4 (acid phosphatase 4) was newly found as a gene causing hypoplastic AI, and it was suggested that mutant forms of ACP4 might affect access to the catalytic core or the ability to form a homodimer. In this study, a Korean and a Turkish family with hypoplastic AI were recruited, and their exome sequences were analyzed. Biallelic mutations were revealed in ACP4 : paternal (NM_033068: c.419C>T, p.(Pro140Leu)) and maternal (c.262C>A, p.(Arg88Ser)) mutations in family 1 and a paternal (c.713C>T, p.(Ser238Leu)) mutation and de novo (c.350A>G, p.(Gln117Arg)) mutation in the maternal allele in family 2. Mutations were analyzed by cloning, mutagenesis, immunofluorescence, immunoprecipitation, and acid phosphatase activity test. Comparison between the wild-type and mutant ACP4s showed a decreased amount of protein expression from the mutant forms, a decreased ability to form a homodimer, and a decreased acid phosphatase activity level. We believe that these findings will not only expand the mutational spectrum of ACP4 but also increase our understanding of the mechanism of ACP4 function during normal and pathologic amelogenesis.